Targeting anti-inflammatory immunonanocarriers to human and murine neutrophils via the Ly6 antigen for psoriasiform dermatitis alleviation. (14th December 2022) - Lin, Cheng-Yu; Yu, Huang-Ping; Chang, Yen-Tzu; Lin, Zih-Chan; Alalaiwe, Ahmed; Hwang, Tsong-Long; Fang, Jia-You
Abstract : Psoriasis is a refractory and difficult-to-treat skin disorder. Abstract : Psoriasis is a refractory and difficult-to-treat skin disorder. The neutrophil-targeting approach represents a promising option for psoriasis therapy. This study developed and examined NIMP-R14-conjugated immunonanoparticles for specific targeting to neutrophils associated with psoriasiform dermatitis. In the process, roflumilast (RFL), as a phosphodiesterase (PDE) 4 inhibitor, was encapsulated in the nanocarriers to assess the anti-inflammatory capability against primary neutrophil activation and murine psoriasiform lesion. The average size and surface charge of the immunonanocarriers were 305 ± 36 nm and −18 ± 6 mV, respectively. The monovalent antibody-conjugated nanoparticles offered precise uptake by both human and mouse neutrophils but failed to exhibit this effect in monocytes and lymphocytes. The intracellular RFL concentration of the immunonanocarriers was five-fold superior to that of the passive counterparts. The immunonanocarriers specifically recognized the neutrophils through the Ly6 antigen with no apparent cytotoxicity. The antibody-conjugated nanoparticles mitigated superoxide anion production and migration of the activated human neutrophils. The in vivo biodistribution in the psoriasiform mice, found using an in vivo imaging system (IVIS) and liquid chromatography (LC)-mass-mass analysis, showed that the antibody conjugation increased the nanoparticle residence in systemic circulation after intravenous administration. On the other hand, most of the nanoparticles were accumulated in the lesional skin after subcutaneous injection. The actively-targeted nanocarriers were better than the free RFL and unfunctionalized nanoparticles in suppressing psoriasiform inflammation. The immunonanocarriers reduced neutrophil recruitment and epidermal hyperplasia in the plaque. Intravenous and subcutaneous treatments with the immunonanocarriers significantly reduced the overexpressed cytokines and chemokines in the inflamed skin, demonstrating that the nanosystems could both systematically and locally alleviate inflammation. The results indicated that the NIMP-R14-conjugated RFL-loaded nanoparticles have potential as an anti-autoimmune disease delivery system for neutrophil targeting.